Upaya Perbaikan Proses Pencatatan Barang di PT. X - Tiono, Jennie; Sutapa, I Nyoman (Jurnal Titra, 2015)
The research was conducted to determine the cause of error in the recording process items and give the solutions. The research analysis is using fishbone diagrams to find the root cause of the problems. The existing problems in the process of receiving and the gemstone is wrong input the destination, wrong input the code, double input code, wrong input quantity measurement. Proposed improvements are the socialization of code standardization, adding data records that have been incorporated into the program, putting work instruction near the computer, and immediately set the unit quantity of gemstone which has been set in the program. The existing problems in stock opname are the amount of items not in accordance with the database and the items do not conform to the code. Proposed improvements are making Kaizen foam and form of lending tools, provide a label that contains the weight of BK, put small items in the plastic and then put in into the rack, and stop the transaction.